Kozmopolitska demokracija: včeraj, danes, jutri, nikoli več? - Pikalo, Jernej (Teorija in praksa, 2009)
The aim of the paper is to reignite the debate on cosmopolitan democracy and global governance that has almost been extinguished since the beginning of the new millennium. The paper stems from the position that the 2008-2009 crisis is a civilisational crisis that requires a change in political relations and global politics. It analyses conceptualisations of cosmopolitan democracy and establishes that they are mainly based on methodological territorialism. Liberal democracy as a form of the organisation of political communities is scrutinised. The paper calls for human rights as an ethical basis of a new global order.
Keywords: Democracy; Demokracija; Globalisation; Globalizacija; globalization; Human rights; Človekove pravice; politična teorija